Diversity of Marine Crabs in Five Different Ecosystems along the Andaman Coastal Research Station for Development and Mu Ko Kam, Ranong Province - Wisespongpand, Puntip; Jaingam, Wachirah; Wongissarakul, Kamonchanok; Kongkaew, Wisai; Ratmuangkhwang, Sahat (Burapha Science Journal, 2026)
The Andaman Coastal Research Station for Development and Mu Koh Kam, Ranong province are fertile crab habitats combining of 5 ecosystems; sandy beach, rocky beach, mangrove, coral reef and offshore. Regarding to its comprehensive environment, 137 species, 82 genera and 33 families were found indicating its high diversity of crabs. The high species richness belonged to Families Xanthidae, Diogenidae and Portunidae with numbers of 18, 18 and 13 species, respectively. In term of ecosystem, offshore was indicated to be the highest species richness followed by rocky beach, coral reef, mangrove, and sandy beach with numbers of 67, 30, 23, 21, and 18 species, respectively. The rare species was at 80.62% of total number of species while species richness of utilization crabs was only at 13.33%. Upon various ecosystems and stations, habitat characteristics has the most impact on community and species diversity. Bannbangkluay offshore ecosystem, had the highest Shannon’s diversity index and species richness index at 10.3683 and 3.3170, respectively. Mangrove in the Southeast of the station had the highest Peilou's evenness index at 0.8860. While sandy beach in this area had exceptional characteristic discovering 4 soldier crabs and 3 land hermit crabs. This study provided checklist of crabs including abundance, distribution, and status. As a result, Andaman Coastal Research Station for Development and Mu Koh Kam, should be promoted as a Biodiversity Important Area (BIA) and remarkable area for future diversity management and conservation to sustain crab biodiversity.